Feasibility of use of color-coded rings by nurse midwives: An appropriate technology based on partographic principles - Asha K Pratinidhi; Shubhada Suresh Javadekar; Aparna Nishikant Shrotri; Sudesh Vijay Gandham; Archana Patil; Krishna S Patil (Wolters Kluwer Medknow Publications, 2013)
Objectives: To study the feasibility of use of color-coded rings as a proxy for partograph for early identification of slow progress of labor. Materials and Methods: Color-coded rings were devised as a tool using appropriate technology to translate the partographic principles into simpler, easy to understand methodology. The rings were in pairs of 4 colors i.e., red, blue, yellow, and green, ranging from 3 cm to 10 cm in diameter with a difference of 4 cm between rings of the same color. The midwife performed p/v examination of the woman in labor to assess the initial cervical dilatation and identify corresponding ring. P/V was to be repeated after 4 hours to reassess the cervical dilatation and compare it with the bigger ring of the same color indicating expected cervical dilatation. If existing cervical dilatation measured lesser, it was interpreted as slow progress of labor indicating referral. Results: 44 women [23 (22.1%) primis and 21 (13%) multis] showed delayed progress of labor as judged by use of color-coded rings. 20 women (4 primis and 16 multis) showed satisfactory progress or delivered by the time arrangements for referral were made. Conclusion: Use of color-coded rings may serve as a valuable tool based on appropriate technology to assess slow progress of labor not only in the hands of nurse midwives but it also can serve as a training tool for TBAs to help facilitate timely referral of such cases.